Effects of Dietary Supplementation of Essential Oils as an Alternative to Antibiotic Growth Promoter on Performance of Commercial Broilers - C, Rajalekshmi; Mishra, Ram Kailash; Savaliya, Fulabhai P; Patel, Atul B; Lunagariya, Pravin M; Bhagora, Nitesh J (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
An experiment was conducted to assess the effects of thyme and peppermint essential oils (EO) as an alternative to antibiotic growth promoter (AGP) on the performance of broiler chicken. Total 256 day-old Vencobb broiler chicks were randomly distributed into eight experimental groups with four replicates of eight birds each. Experimental groups were fed with control diet without supplementation of AGP and essential oils (T1), BMD (Bacitracin Methylene Disalicylate) antibiotic @ 500 mg/kg diet (T2), thyme essential oil @ 150 mg/kg diet (T3), 200 mg/kg diet (T4), 250 mg/kg diet (T5), peppermint essential oil @ 200 mg/kg diet (T6), 250 mg/kg diet (T7) and 300 mg/kg diet (T8). The supplementation of thyme oil @ 200 mg/kg and peppermint oil @ 300 mg/kg broiler diet significantly (p<0.05) improved b.wt. and b.wt gain. The peppermint oil supplementation @ 300 mg/kg was found to be more beneficial when compared among different oil-supplemented groups. The feed conversion ratio was significantly (p<0.05) improved with peppermint oil supplementation @ 300 mg/kg diet. A significant (p<0.05) reduction in the mean abdominal fat was observed in diet supplemented with higher levels of thyme oil (@ 250 mg/kg diet) and peppermint oil (@ 300 mg/kg diet). Return over feed cost was the highest in broilers assigned diet with AGP; however, it was statistically similar to the basal diet. Considering the net return over fed cost of broilers, use of thyme oil was uneconomical, but supplementation of peppermint essential oil @ 200 and 300 mg/kg diet increased the net return over feed cost and were economical, however less as compared to T1 and T2.